Perceptions And Roles Of Indonesian Journalists In Covering Environmental Problems In Indonesia - Agustina, Anna (2017)
This study aims to examine Indonesian journalists perceptions of and roles in environmental issues, and identify the factors that drive journalists to act to mitigate environmental problems. A grounded theory methodology was used to collect and analyse empirical data. First, theoretical sampling was conducted to identify informants for the study. Then, in-depth interviews were conducted with 30 informants. The "grounded theory" method has succeeded in building a theoretical framework on perceptions and the role of Indonesian journalists on environmental issues. The study found that all Indonesian journalists perceive environmental problem is challenging. However, when it comes to the role of journalists on it, there are important factors that differentiate general and environmental journalists – passion, knowledge, exposure to environemtnal issues, and environmental network.